2020
DOI: 10.1111/jfpp.14401
|View full text |Cite
|
Sign up to set email alerts
|

Physical and antibacterial properties of corn distarch phosphate/carboxymethyl cellulose composite films containing tea polyphenol

Abstract: Antibacterial packaging films were developed by incorporating tea polyphenol (TP) into corn distarch phosphate (CDP)/carboxymethyl cellulose (CMC) films via solvent casting. Incorporation of TP had a great influence on the physical properties of the composite films. The prepared composite films were evaluated by scanning electron microscopy and Fourier transform infrared spectroscopy, and their physical properties, moisture barrier properties, and antibacterial activities were investigated. Microstructural stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Hanani et al [ 19 ] reported that fish gelatin containing pomegranate ( Punica granatum L.) peel powder has great potential as an active film with antioxidant and antimicrobial properties, and thus, it can help maintain the quality and prolong the shelf life of food products. Shao et al [ 20 ] added tea polyphenol (TP) into corn distarch phosphate (CDP)/carboxymethyl cellulose (CMC) composite films that showed excellent antibacterial activity against Staphylococcus aureus , Bacillus subtilis , and Escherichia coli . Fang et al [ 21 ] produced starch-based composite films incorporated with salicylic acid (SA) to which the addition of waxy maize starch nanoparticles/κ-carrageenan (WMSNs/KC) significantly increased the tensile strength, water vapor barrier, and thermal stability, while the transparency and elongation at break decreased slightly.…”
Section: Introductionmentioning
confidence: 99%
“…Hanani et al [ 19 ] reported that fish gelatin containing pomegranate ( Punica granatum L.) peel powder has great potential as an active film with antioxidant and antimicrobial properties, and thus, it can help maintain the quality and prolong the shelf life of food products. Shao et al [ 20 ] added tea polyphenol (TP) into corn distarch phosphate (CDP)/carboxymethyl cellulose (CMC) composite films that showed excellent antibacterial activity against Staphylococcus aureus , Bacillus subtilis , and Escherichia coli . Fang et al [ 21 ] produced starch-based composite films incorporated with salicylic acid (SA) to which the addition of waxy maize starch nanoparticles/κ-carrageenan (WMSNs/KC) significantly increased the tensile strength, water vapor barrier, and thermal stability, while the transparency and elongation at break decreased slightly.…”
Section: Introductionmentioning
confidence: 99%
“…coli is through the destruction of bacterial cell membranes, inhibiting the ability of the bacteria to bind to host cells and each other to form biofilms (Reygaert, 2014). The high content of peptidoglycan in the cell wall of S. aureus cannot protect the cell, TP is easy to transfect cells, inhibit nucleic acid, interfere with the energy system, and achieve the antibacterial effect (Shao et al., 2020). It is also observed that the initial antibacterial effect of the uniaxial antibacterial pad is significantly higher than that of the coaxial antibacterial pad.…”
Section: Resultsmentioning
confidence: 99%
“…As the concentration of TP increased, the inhibitory activity of the CDP/CMC/TP composite membrane significantly increased (P < 0.05; Shao et al, 2020). TP has a wide range of applications in the preservation of raw meat due to its good antibacterial effects.…”
Section: Tea Polyphenolmentioning
confidence: 95%
“…Shao et al (2020) prepared the antibacterial packaging film by solvent casting method of TP and corn expanded phosphoric acid (CDP)/carboxymethyl cellulose (CMC) to inhibit S. aureus, Bacillus subtilis and E. coli. It was found that it has a stronger inhibitory effect on Grampositive bacteria, compared with Gram-negative bacteria.…”
mentioning
confidence: 99%